ANALISIS KEMAMPUAN KOGNITIF PESERTA DIDIK DALAM PROSES PEMBELAJARAN EKONOMI KELAS XI IPS SMA WISUDA - Herlina Gowen; Sulistyarini Sulistyarini; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study focuses on "Analysis of Cognitive Ability of Students in the Economic Learning Process in Class XI IPS at SMA Wisuda Pontianak". The purpose of this study are, 1) the ability to understand students in the economic learning process in class XI IPS, 2) the ability to remember students in the economic learning process in class XI IPS, 3) the ability to evaluate students in the economic learning process in class XI IPS. Descriptive research method with a qualitative approach. The datasource of this study were teachers and students of class XI IPS. Data collection techniques used are direct communication techniques, indirect communication techniques, measurement techniques and documentary techniques. Observation data collection tools, interview guides, test questions, and documentation. Research results that; 1) the ability to understand students in the category of "very good" ie an average of 77% study. 2) the ability to remember students in the category of "good" ie an average of 62% study. And 3) the ability to evaluate learners in the "low" category which is an average study of 35%. The results of thisstudy are expected to be used as a reference or benchmark for students in the future in order to improve the cognitive abilities of students on the ability to evaluate.Keyword : Cognitive Ability, Economic Education